Researching the Future Pedagogues' Lideship Skills: Validation of the Inventory of Student Lidership Outcomes - Milena M. Letić Lungulov; Saška S. Radujkov (University of Belgrade, Teacher Education Faculty, 2024)
The paper looks at the leadership skills of the future pedagogues as a prerequisite for their success and coping in a professional environment. In addition, the goal is to examine the metric characteristics of an adapted version of the Inventory of Student Leadership Outcomes. Leadership skills are operationalised in terms of eight variables related to: organisation and planning, awareness of diversity, self-management, self-confidence, use of technologies, cognitive development and critical analysis, interpersonal communication, problem solving and decision-making. The research was conducted on a sample of 194 respondents who are studying pedagogy at the Faculty of Philosophy of the University of Novi Sad. The results indicate that the original eight-factor structure of the instrument has been confirmed, and that the Inventory of Student Leadership Outcomes, even in its shorter form, is a reliable and valid instrument suitable for application in various educational contexts. It was determined that the students of pedagogy, viewed as a whole, possess leadership potential, which is reflected in above-average developed leadership skills. According to the respondents' self-assessment, the awareness of diversity is most emphasised among the examined variables, while interpersonal communication skills are the weakest, although still above average. The results are satisfactory, but they leave room for action in terms of improving the professional training of the future pedagogues, which would entail nurturing and developing the skills and personality traits necessary for establishing, building, and improving relationships with other participants in the educational process.